Apathy as a herald of cognitive changes in multiple sclerosis: A 2-year follow-up study. (March 2020) - Raimo, Simona; Spitaleri, Daniele; Trojano, Luigi; Santangelo, Gabriella
Background: Behavioral symptoms, such as apathy and depression, are common in multiple sclerosis (MS) but their relationship with cognitive and clinical characteristics often remains underinvestigated and not monitored over time. Objective: The aim of this study was to assess the evolution of cognitive profile of patients affected by MS in relation to apathy and depression using a 2-year follow-up study. Methods: Two years after the first assessment, 100 of 125 MS patients were re-evaluated on a comprehensive neuropsychological battery, and on specific scales for assessment of apathy (Apathy Evaluation Scale—Self-reported) and depression (Hamilton Depression Rating Scale). Results: After 2 years (T1), we found a relatively consistent prevalence of apathy (about 40%) and a reduction in prevalence of depression (from 44% to 30%). Higher level of apathy at baseline predicted the progressive cognitive changes at follow-up; and patients with apathy without depression ("pure" apathy) than patients without apathy had poorer performance on the interference task of the Stroop test assessing inhibitory control. Conclusion: The present results suggested that apathy in MS was associated with more severe executive dysfunctions (in particular cognitive control). Apathy rather than depression predicted cognitive impairment in MS over time.